Rainfall Erosivity and Sediment Dynamics During Kagbeni Flood in Mustang, Nepal - Acharya, Sunita; Baniya, Binod; Acharya, Sunil; Prajapati, Meera; Bhatta, Mahesh (Journal of Hydrology and Meteorology, 2025)
An extreme flood occurred during August 13, 2023 in the Kagbeni, Mustang,during the flood event, a large volume of sediments were eroded due to the high rainfall intensity. In this study, rainfall erosivity i.e. capacity of rain causing soil erosion using precipitation records (1972–2023) and post flooding event sediment analysis were estimated. The research aims to understand how rainfall patterns particularly during extreme flooding, influence erosion processes and sediment transport. Results showed that annually precipitation increased at a rate of 3.34 mm yr-1 during 1972 to 2023 with a significantly increasing trend in monsoon and pre-monsoon season. The Kagbeni flood on August 13, occurred despite moderate daily rainfall of 25 mm and water level of 2.5 m compared to month’s peak precipitation of 62.3 mm, suggesting that temporary river damming played a crucial role in triggering the event. The Mann-Kendall trend test applied to precipitation data highlights variability in seasonal precipitation patterns and increasing intensity during flooding time. Using Modified Fournier Index (MFI) models for rainfall erosivity reveals substantial variability with erosivity values ranging from a minimum of 60.621 MJ mm ha⁻¹ h⁻¹ year⁻¹ to a maximum of 9244.81 MJ mm ha⁻¹ h⁻¹ year⁻¹. Absence of a significant temporal trend in the Mann-Kendall analysis suggests extreme events are episodic rather than a systematic change in erosivity patterns. The flooded year, erosivity index level (123.09 MJ mm ha⁻¹ h⁻¹) exceeding 120 represent a critical threshold for soil erosion potential with cumulative rainfall erosivity of 1223.49 MJ mm ha⁻¹ h⁻¹ highlighting single-month events significantly impacting the overall annual erosion potential. Sediment analysis using ImageJ software indicates upstream areas such as Jhong Khola and Muktinath Khola contain coarser sediments (120–140 mm range) while downstream locations like Kagbeni Confluence and upstream site showed finer sediments passing. The increasing rainfall intensity was responsible for sediment transport during flooding. Thus, rainfall erosivity is found higher in the basin during monsoon season.